DIFFERENT STRATEGIES OF ADAPTATION AND READABILITY OF PERSONALITY IN THE CONDITIONS OF TRANSFORMATION OF THE MODERN ENVIRONMENT - Zavatska, Natalia Yevhenivna (Psychological Prospects Journal, 2013)
The article presents the socio-psychological analysis of the strategies of social adaptation and re-adaptation of the individual in the conditions of the transformation of modern society: individual, group, societal. The peculiarities of information influence as a condition and factor of adaptive processes are revealed. It is shown that the main social and psychological factor of social adaptation of personality is its adaptive potential. The content of the social rehabilitation program aimed at increasing the adaptation potential of socially disadapted individuals through the special organization of the rehabilitation social environment according to the personality characteristics of the readaptants is disclosed. It is substantiated that social rehabilitation of an individual is effective when it is carried out systematically at the level of primary re-adaptation, basic level and level of post-adaptation and is constructed taking into account indicators of levels of adaptation potential and adherence to the principles of equivalence, dynamism, differentiated forecasting and perspective.